Effect of Gypsum Content Variation on The Compressive Strength of Lightweight Non-Structural Bricks Made from Rice Husk and Cement - Indrayuni, Putri; Supriyadi, Asep; Sutandar, Erwin (Jurnal Teknik Sipil, 2025)
Rapid urbanization and population growth have led to a significant rise in the demand for building materials, thereby contributing to increased environmental impacts due to the widespread use of conventional materials such as concrete blocks and red bricks. These materials are known for their heavy weight and energy-intensive manufacturing processes, resulting in high carbon emissions and environmental degradation. In response to these concerns, this study explores an alternative in the form of rice husk lightweight bricks enhanced with gypsum casting as a partial cement substitute. The objective is to investigate the effects of gypsum casting on the physical and mechanical properties of the bricks and to evaluate their compliance with the Indonesian National Standard SNI 8640:2018 for lightweight wall bricks. Five variations of gypsum casting"”0%, 15%, 35%, 40%, and 45%"”were analyzed. Results show that bricks with 15% gypsum exhibited the best performance in terms of volume weight (998.438"“1.054.063 kg/m ³), compressive strength (4.326"“6.192 MPa), and fire resistance (up to 489.13 °C). All specimens displayed 0% drying shrinkage and acceptable levels of water absorption, sound resistance, and heat insulation, demonstrating the feasibility of using gypsum-modified rice husk bricks as sustainable building materials.